Implementing Dictogloss Through Collaborative Learning to Develop Writing skill in the English Classroom - Jarrin Escobar, Veronica Gissela (2011)
1. The concep of writing 2. Dictogloss 3. Dictogloss and current trends in second language teaching 4. Cooperative learning 5. Conclusions and Recommendations